The Post-American World : And the Rrise of the Rest - Zakaria, Fareed (London Penguin Books, 2011)
The growth of countries such as India, China, Brazil, Russia, South Africa and Kenya generates a fresh landscape. This book shows how the West must transform its global strategy, moving from a position of hegemony to one that recognizes this seismic power shift.
Include Notes and Index.
Keywords: Twenty-first century -- Forecasts. -- International relations -- Forecasting. -- International economic relations -- Forecasting